Development of a doctor following mobile robot with mono-vision based marker detection - Mohd Nazri, Abu Bakar; Ramachandran, Nagarajan, Prof. Dr.; Abdul Rahman, Mohd Saad, Prof. Madya Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/